2017
DOI: 10.29252/3dj.6.3.49
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Maxillary Sinus Floor and Posterior Maxillary Teeth Roots Using Panoramic and Cone Beam Computed Tomography

Abstract: Understanding the anatomical and pathological relationships between posterior teeth or edentulous area with maxillary sinus is essential for diagnosis and treatment management.The present study aimed to assess the relationship between maxillary sinus floor and posterior teeth roots using panoramic radiography and Cone Beam Computed Tomography (CBCT). Materials and Methods: In this analytical cross-sectional study, 440 maxillary first and second premolars, and first and second molars of 55 patients were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 13 publications
0
5
0
9
Order By: Relevance
“…Sensitivity was (97.5%), specificity was (16.2%), positive predictive value was (79.3%) and negative predictive value was (66.7%). Results of the model presented in table (3) showed that age, sex, presence of periapical lesion and dental caries all had a significant effect on MT occurrence (p<0.05). It was found that a year increase in age increased the odds of MT by 1.05, males had 2.86 higher odds of having MT than females, presence of periapical lesion increased the odds of MT by 6.38, and the presence of dental caries increased the odds of MT by 2.87.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sensitivity was (97.5%), specificity was (16.2%), positive predictive value was (79.3%) and negative predictive value was (66.7%). Results of the model presented in table (3) showed that age, sex, presence of periapical lesion and dental caries all had a significant effect on MT occurrence (p<0.05). It was found that a year increase in age increased the odds of MT by 1.05, males had 2.86 higher odds of having MT than females, presence of periapical lesion increased the odds of MT by 6.38, and the presence of dental caries increased the odds of MT by 2.87.…”
Section: Resultsmentioning
confidence: 99%
“…CBCT scans were chosen according to the inclusion and exclusion criteria previously mentioned in the methodology chapter. The age of the patients who took part in the research started from 20 years because it is the estimated age when the maxillary sinus growth stops [3,6] , further second premolar, first and second molar teeth were chosen for assessment due to their close approximation to the sinus floor [3,37,38] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies used different scoring systems to categorize the sinus-root relation in different populations [8][9][10][11][12][13][14][15]. The simplest of all these systems consists of three classes, class 1: root tip is outside the sinus, class 2: root tip is against the sinus wall, and class 3: root tip is in the sinus [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%